The Development of the Learning Management System-Based Übungtest Schreiben at Level A1 for Students of PASCH School SMAN 1 Malang - Lutfi Anastia Ardiningrum; Dewi Kartika Ardiyani (Randwick International of Education and Linguistics Science Journal, 2023)
This research and development aim to understand the process of developing Übungtest Schreiben to improve the writing skills of PASCH A1 students using the Learning Management System (LMS) and to find out the effectiveness of its use. By improving students' writing skills, it is hoped that the LMS-based Übungtest Schreiben can assist students in preparing for the German A1 exam. The background of this research and development is the situation of the PASCH A1 students who need a lot of writing exercises before taking the German language exam Goethe-Zertifikat A1 which corresponds to the Common European Framework of Reference for Languages (CEFR). This research and development uses the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) and the product is Moodle-based Übungtest Schreiben that consists of a module, Schreibübungen, and Schreibtest/Modelltest for PASCH students at SMA Negeri 1 Malang. The type of data in this development is qualitative data and supported by quantitative data. Qualitative data is obtained in the analysis, design, development, and evaluation phases with a logbook and a questionnaire for material validation and the data is analyzed using the descriptive analysis technique. Quantitative data is obtained through the adequacy test in the implementation stage and the effectiveness test of Übungtest Schreiben. Based on the results of the material validation, test, and student questionnaires, LMS-based Übungtest Schreiben is very adequate and effective as a digital learning media to improve writing skills.